Peningkatan kemampuan penggunaan huruf kapital dan tanda baca dalam menulis karangan sederhana melalui model think talk write pada peserta didik kelas III sekolah dasar - Hesti Khasyanah Putri; Rukayah Rukayah; Sularmi Sularmi (Didaktika Dwija Indria, 2019)
Abstract. The purpose of this research is improving the ability to uses capital letters and punctuation in writing simple essays by applying think talk write model. This research is Classroom Action Research with two cycles. The subjects of this research were students of the 3th students at SD Negeri Pajang II Surakarta in the 2018/2019 academic year, totalling 27 students. This research uses data collection techniques in the form of interview, observation, tests, and analysis document with data analysis of source triangulation and technique triangulation. The analysis of the data used is the interactive analysis model of Miles-Huberman. The first cycle resulting in a percentage of 66.66% in classical, and the study continued with the second cycle with the percentage of 88.89% in classical terms. Based on the result of the research, it can be conclude that the ability to use capital letters and punctuation in writing simple essays on 3th students of SD Negeri Pajang II Surakarta in the 2018/2019 academic year can be improved through the Think Talk Write model.Keywords: capital letter, punctuation, simple essays, Think Talk Write model